ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BELAJAR BAHASA JAWA PESERTA DIDIK SEKOLAH DASAR - Inayatul Fauziah; Atikah Mumpuni; Rila Melyana Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the factors that influence learning interest and teachers' efforts to increase interest in learning Javanese in elementary school students. This study identified various problems related to the low interest in learning Javanese in elementary schools. In this study, the Literature Review method was used to review various research results and relevant sources on interest in learning Javanese. These sources included scientific journal articles, books, and academic publications relevant to the research topic. The results showed that there are internal and external factors that influence interest in learning Javanese. Internal factors include students' attention, self-confidence, and desire to learn, while external factors include learning strategies, the use of learning media, the environment, and language habits.